2001
DOI: 10.1046/j.1365-2958.2001.02718.x
|View full text |Cite
|
Sign up to set email alerts
|

Replication arrests during a single round of replication of the Escherichia coli chromosome in the absence of DnaC activity

Abstract: We used a flow cytometric assay to determine the frequency of replication fork arrests during a round of chromosome replication in Escherichia coli. After synchronized initiation from oriC in a dnaC(Ts) strain, non‐permissive conditions were imposed, such that active DnaC was not available during elongation. Under these conditions, about 18% of the cells failed to complete chromosome replication. The sites of replication arrests were random and occurred on either arm of the bidirectionally replicating chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 61 publications
9
61
0
Order By: Relevance
“…The fact that the number of two-chromosome cells does not reach zero during incubation at a non-permissive temperature in the control could be a result of incomplete replication in some of the cells. It has previously been shown that lack of active DnaC during elongation leads to a failure to complete replication in 18 % of cells, because of the lack of loading of DnaC by the primosomal proteins (Maisnier-Patin et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the number of two-chromosome cells does not reach zero during incubation at a non-permissive temperature in the control could be a result of incomplete replication in some of the cells. It has previously been shown that lack of active DnaC during elongation leads to a failure to complete replication in 18 % of cells, because of the lack of loading of DnaC by the primosomal proteins (Maisnier-Patin et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…As both transcription and the insertion of newly transcribed-translated proteins into membrane (transertion) have been implicated as mechanisms contributing to bacterial chromosome segregation (12,31,45,49,61), we wished to test the consequence of inhibiting transcription (and thereby ongoing transertion) on segregation of ori loci. To do so, we synchronized cells for DNA synthesis using dnaC(Ts) mutation (40) and treated them with rifampin (300 g/ml) to block transcription. dnaC(Ts) mutant cells were grown exponentially at 30°C and then shifted to the nonpermissive temperature (37°C) at an A 600 of ϳ0.1 to block replication initiation but allow completion of ongoing rounds of DNA synthesis.…”
Section: Vol 192 2010 E Coli Origin Segregation 6147mentioning
confidence: 99%
“…A substantial fraction of replication forks stall or collapse at sites of DNA damage during bacterial DNA replication (1)(2)(3). Potential blocks to replication include non-coding lesions in the DNA template, DNA strand breaks, or proteins bound to DNA ahead of the replication fork.…”
mentioning
confidence: 99%